2015
DOI: 10.1002/cpe.3589
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐inspired cost‐aware optimization for data‐intensive service provision

Abstract: The use of Big Data and the development of cloud computing have led to greater dependence on dataintensive services. Each service may actually request or create a large amount of data sets. The scope, number, and complexity of data-intensive services are all set to soar in the future. To compose these services will be more challenging. Issues of autonomy, scalability, adaptability, and robustness, become difficult to resolve. Bio-inspired algorithms can overcome the new challenging requirements of data-intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In addition, we proposed a multi-objective ant colony system for data-intensive service concretization [75], where we focused on the scalability and adaptability of service concretization, and particular attention is paid to multiobjective optimization related to cost and QoS attributes. Summary of our current work can be found in [76].…”
Section: Pso Population Sizementioning
confidence: 99%
“…In addition, we proposed a multi-objective ant colony system for data-intensive service concretization [75], where we focused on the scalability and adaptability of service concretization, and particular attention is paid to multiobjective optimization related to cost and QoS attributes. Summary of our current work can be found in [76].…”
Section: Pso Population Sizementioning
confidence: 99%
“…. , r}) are the maximum and minimum possible aggregated values of the k-th QoS attributes for the composite service CS, which can be estimated by (6).…”
Section: Utility Functionmentioning
confidence: 99%
“…5 already proved that it was useful for service management and discovery to add biological mechanisms to services. In our previous work, 6 we have presented a hierarchical taxonomy of Web service composition approaches and provided a detailed analysis of each approach. Then we found that the bio-inspired algorithms could overcome the challenging requirements of the data-intensive service provision.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al . discussed single‐objective and multi‐objective data‐intensive service provision problems based on bio‐inspired algorithms . They also propose an ant‐inspired negotiation approach.…”
mentioning
confidence: 99%
“…Bio-inspired algorithms can overcome the new challenging requirements of data-intensive service provision. Wang et al discussed single-objective and multi-objective data-intensive service provision problems based on bio-inspired algorithms [9]. They also propose an ant-inspired negotiation approach.…”
mentioning
confidence: 99%